Diagnostic Accuracy of Ultrasonography in Contrast to Enhanced Computed Tomography Scan in Evaluation of Focal Renal Masses - Sohail, Mairah; Nayyar, Shaista (Indus Journal of Bioscience Research, 2025)
Background: Focal renal masses need precise characterization with imaging and accurate imaging to distinguish benign lesions and malignancy to establish appropriate clinical management. Aim of the study is to determine the diagnostic accuracy of ultrasonography in comparison with contrast-enhanced computed tomography (CECT) in the evaluation of focal renal masses. Methodology: This study was carried out at PAF Hospital, Islamabad, during a period of 5th January 2024 to 30th September 2024. One hundred and ten (110) patients aged 16-60 years with suspected focal renal masses were recruited using non-probability consecutive sampling. Lesions on both modalities were classified as benign and malignant. Quantitative variables were described in terms of a mean and standard deviation and qualitative variables represented frequencies and percentages. Diagnostic accuracy indices such as sensitivity, specificity and positive predictive value, negative predictive value and overall accurate were computed through cross-tabulation. Results: The mean age of the patients was 41.68 ± 12.84 years, while the mean mass size was 5.00 ± 1.89 cm. Of the 110 patients, 61 (55.5%) were male and 49 (44.5%) were female. On CECT, 21 (19.1%) lesions were malignant and 89 (80.9%) were benign. On ultrasonography, 26 (23.6) were malignant and 84 (76.4) benign. Cross-tabulation showed 17 true positives, 80 true negatives, 9 false positives, and 4 false negatives. Ultrasonography demonstrated a sensitivity of 80.95%, specificity of 89.89%, positive predictive value of 65.38%, negative predictive value of 95.24%, and overall diagnostic accuracy of 88.18% in detecting malignant focal renal masses. Conclusion: Ultrasonography had a good overall diagnostic performance in the assessment of focal renal masses, a high specificity and a negative predictive value. It also seems to be a trusted first line imaging modality to determine the first assessment of renal masses particularly ruling out malignancy. Nevertheless, suspicious or indeterminate lesions only need confirmation by contrast-enhanced computed tomography to determine characterization